ANALISIS PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, AGENCY COST, LIKUIDITAS TERHADAP KINERJA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2015-2019 - Mia Audina (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to examine the effect of capital structure, firm size, agency cost and liquidity on company performance. Researchers found differences in results between previous studies which are strong reasons why this research is feasible. The sample includes 8 banking sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2015-2019. In this study, capital structure is proxied by using the Debt to Equity Ratio (DER), company size is proxied by using (Size), agency cost is proxied by using Free Cash Flaw (FCF), and liquidity is proxied by the current ratio. The method of analysis in this research is descriptive statistical test, classical assumption test and multiple regression analysis using the SPSS application. The results showed that the independent variables, namely capital structure, agency cost have a positive and significant effect on company performance, while the independent variables, namely company size and liquidity, have a negative and significant effect on company performance. Keywords : Struktur modal,ukuran perusahaan, agency cost, likuiditas, kinerja perusahaan.